Tribological properties of composite multilayer coatings - Woldegebriel Gebretsadik, Daniel (2009)
This research project was done in Tribolab at Luleå University of Technology. The research focused primarily on the tribological properties of graded multilayer coatings. Mainly friction and wear behavior of the graded multilayer with a sequence of MoS2:Ti/MoS2:TiBN/TiBN/TiB2/Ti deposited on tool steel substrate was studied. The deposition technique used to prepare the test specimens was Closed-Field Unbalanced Magnetron Sputtering under different deposition parameters. The tribological properties were studied under different conditions by varying important parameters such as temperature and load. The wear mechanism was also investigated with the help of Scanning Electron Microscopy. The experimental results show that the multilayer coating posses important tribological properties. For instance, the friction coefficient values were found to be very small at room temperature and increased significantly at higher temperature. The durability of the multilayer coating was also found to be dependent on the temperature. The effect of applied load was also manifested on the friction coefficient of the coatings. The hardness of the multilayer coating was also found to be dependent on temperature. The results show that the coating exhibited important tribological properties. Validerat; 20101217 (root)